Fabrication of cotton/polyethylene glycol/stainless steel wire friction spun composite yarn and its application in electrothermal phase change textile. (June 2022) - Yu, Lixiang; Qin, Xiaohong; Ke, Guizhen; Tang, Jiani; Wang, Yu
Abstract: This work successfully fabricated a textile with phase change and electrothermal function using a novel method. First, a core-sheath-structure composite yarn (cotton/polyethylene glycol/cotton/stainless steel wire) was prepared through friction spinning and sizing. Secondly, the composite yarn was weaved with 2-ply cotton yarns to form an electrothermal phase change textile. The resulting composite fabric possesses good phase change reliability after 50 heating/cooling cycles and exhibits great electrothermal repeatability after 50-cycle durability test. The addition of polyethylene glycol can increase the maximum surface temperature of the fabric (e.g., the highest temperature of the fabric can reach 66 °C when the voltage is 5 V, while the highest temperature of the blank sample is 56 °C), extend the heat time of composite fabrics, alleviate dramatic temperature fluctuations while charging and discharging, and improve the surface temperature distribution uniformity of the fabric. The described method displays a new platform for developing electrothermal heating elements utilized in flexural heaters, medical electrothermal, and defrosting. Graphical abstract: Image 1 Highlights: The described method is simple in process, low in cost, and easy in industrialization.